Proposta de um sistema de indicadores de desempenho para avaliação de estações de tratamento de esgotos do Distrito Federal - Izabela Pinheiro Alves Felipe Barros (2013)
This study proposes a performance indicators system to assess municipal waste water treatment plants (WWTP), taking as a case study plants located in the Federal District, Brazil, from the perspective of regulation. To examine the applicability of the developed system, called SISTEMA ID-ETE, it was used for evaluation of three waste watertreatment plants from that region, representing different sizes and processes treatment. In order to subsidize the development of the indicators system, was carried, first, a performance analysis of three treatment plants selected as researchs objects Brasília Norte, Samambaia and São Sebastião using statistics tools and survey of plants features and operating conditions in technical visit. These plants were selected because they have different sizes and treatment processes. The survey of performance indicators of waste water treatment plants reported in the literature covered 16 sanitation, national and international, organizations with only 4 specific for evaluation of these structures. In a total of 713 indicators, 276 specifics to WWTP were identified. When excluded the coincidents, were obtained of different types 163 indicators. When analyzing the selected indicators from the perspective of regulation, associating them with 5 goals and 10 previously identified evaluation criteria, 39 performance indicators were selected and adapted. In addition to these indicators, context factors and a classification of data quality are also in the SISTEMA ID-ETE. The application of the system showed that only 28 indicators could be calculated under the present study. The results showed that the SISTEMA ID-ETE is able to evaluate accordingly waste water treatment plants of different sizes and processes and also analyze comparatively these structures.